The Effect of Implementing the Practicum Method on Students' Learning Motivation in Reaction Rate Material - Seto Hariono; Eny Enawaty; Rachmat Sahputra (Universitas Pendidikan Mandalika, 2026)
This study aims to determine the effect of the application of the practicum method on student learning motivation in the reaction rate material of class XI of SMA Negeri 11 Pontianak. This study uses a quantitative approach with a quasi-experimental design with a one group pretest–posttest design model. The research sample consisted of 36 students of class XI Chemistry 2 who were selected using the purposive sampling technique. Data collection was carried out using a learning motivation questionnaire consisting of 25 statements on a Likert scale. Data analysis included normality test, homogeneity test, Wilcoxon test, and N-Gain calculation. The results showed that the average student learning motivation increased from 61.02% (high category) before treatment to 87.36% (very high category) after the application of the practicum method. The increase occurred in all indicators of learning motivation with an increase of 23.77% to 30.19%. The results of statistical tests also showed a significant difference between learning motivation before and after treatment. These findings show that practicum activities not only increase students' motivation to learn, but also help students understand the concept of reaction rate more concretely through hands-on experience. The implication of this study is that the practicum method can be an effective learning strategy to increase student engagement, strengthen the understanding of abstract chemistry concepts, and create more active and meaningful learning in the classroom.